Higher serum level of CTRP15 in patients with coronary artery disease is associated with disease severity, body mass index and insulin resistance. (2nd January 2022) - Shokoohi Nahrkhalaji, Abolfazl; Ahmadi, Reza; Fadaei, Reza; Panahi, Ghodratollah; Razzaghi, Malihe; Fallah, Soudabeh
Abstract: Background: CTRP15 is a prologue of adiponectin which has shown to have favourable effects on glucose and lipid metabolism. Studies have reported lower levels of CTRP15 in T2DM and metabolic syndrome; however, its circulating levels have not been evaluated in CAD patients. Methods: This case–control study was conducted on 190 angiographically confirmed coronary artery disease (CAD) patients and 70 controls. Serum levels of CTRP15, adiponectin, TNF-α, and IL-6 were measured using the ELISA technique. Results: CTRP15 was shown to occur in higher levels in CAD patients compared with controls. In CAD patients, CTRP15 showed a positive correlation with BMI, FBS, insulin, HOMA-IR, IL-6, and TNF-α and a negative correlation with HDL-C and adiponectin. Conclusion: Elevated levels of CTRP15 in CAD patients and the relation of CTRP15 with pathogenic conditions such as insulin resistance, inflammation, and decreased adiponectin and HDL-C suggest a possible compensatory response to these conditions in CAD patients.